2020
DOI: 10.1108/ijshe-03-2020-0089
|View full text |Cite
|
Sign up to set email alerts
|

Synergizing education, research, campus operations, and community engagements towards sustainability in higher education: a literature review

Abstract: Purpose The UN proclamation of 2005–2014 as the decade of education for sustainable development has been instrumental in creating awareness and driving higher education institutions (HEIs) in integrating sustainability into their system. The purpose of this paper is to explore and encapsulate practices adopted by universities and colleges across the globe in integrating sustainability in education (here refers to curriculum and peda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 223 publications
(220 reference statements)
1
96
0
7
Order By: Relevance
“…The investigation also reports the results of these efforts. A detailed examination of 229 peer-reviewed research studies in the 2005-2018 time period selected from 44 journals in a recent study by Menon and Suresh [16] indicated that the implementation of sustainable development has been limited to its integration into teaching and learning and other aspects of educational practices. This examination demonstrated that only a few universities have been successful in implementing it holistically, that is, integrating all the triple bottom line dimensions in balance.…”
Section: Call For Action By Universities and An Opportunity For Universitiesmentioning
confidence: 99%
“…The investigation also reports the results of these efforts. A detailed examination of 229 peer-reviewed research studies in the 2005-2018 time period selected from 44 journals in a recent study by Menon and Suresh [16] indicated that the implementation of sustainable development has been limited to its integration into teaching and learning and other aspects of educational practices. This examination demonstrated that only a few universities have been successful in implementing it holistically, that is, integrating all the triple bottom line dimensions in balance.…”
Section: Call For Action By Universities and An Opportunity For Universitiesmentioning
confidence: 99%
“…Although the public behaviour of students is sometimes a concern (e.g. hazing) (Salinas and Boettcher, 2018), universities are generally considered to contribute positively to local communities and to have good relationships with local residents (Sedlacek, 2013;Perry and Wiewel, 2015;Too and Bajracharya, 2015;Menon and Suresh, 2020). However, as large footprint projects, many universities (campus, staff and students) may have caused the physical displacement of pre-existing residents and are likely to create various environmental and social impacts that affect the host community over time (Posner and Stuart, 2013;Vanclay, 2017a).…”
Section: Social Impacts and The Sustainability Expectations Of Transnational Universitiesmentioning
confidence: 99%
“…Contrary to the wider discourse on sustainability in HEIs, still dominated by campus operations and education for sustainability [71,72], the literature on holistic approaches puts emphasis on content factors comprising the institutional framework. This confirms the idea that vision, strategy, policies, and governance structures are significant leverage points for transforming an organizational system, since they can influence decision-making, resource distribution, and stakeholder behaviors across all other sub-systems and the organization as a whole [20,73].…”
Section: Embedding Sustainability In the Institutional Frameworkmentioning
confidence: 99%
“…However, since English language dominates the international scientific literature, the bias should not be very pronounced [81]. A further limitation, also found in the broader sustainability in higher education literature, is the geographical coverage of publications, featuring mainly European and North American researchers and institutions [41,71]. This is mitigated by articles taking an international scope, but studies from Asian and African countries are still missing.…”
Section: Limitationsmentioning
confidence: 99%